PENENTUAN SIFAT TEKNIS TANAH JENUH SEBAGIAN DAN ANALISIS DEFORMASI LERENG AKIBAT PENGARUH VARIASI HUJAN - Ahmad RIFA’I; Kabul Basah SURYOLELONO; Sony PRAMUSANDI (Jurnal Poli-Teknologi, 2011)
Abstract Recently, landslides often occurs in natural slope in Indonesia, which is associated with the coming rainy season . The increment of ground water level cause by rainfall is affected the properties and behavior of soil especially the unsaturated soil. Generally, the stability of slope is evaluated based on safety factor, but the deformation occured at the soil can also be a good interest in assesing the stability of slope. This research is focused to observe the change of pore water pressure and ascoociate deformation considering the hydro-mechanical properties of unsaturated soil due to the effect of varies rainfall. In this research, numerical simulation was carried out to analysis the deformation of the slope affected by pore water pressure change due to rainfall using software-based Finite Element Method of SIGMA/W and SEEP/W from GEO-SLOPE 2004. Unsaturated soil properties, such as Soil Water Characteristic Curve (SWCC) and Hydraulic Conductivity function are obtained from laboratory test and also predicted based on grain-size distribution using psycho-empirical method in SOILVISION Database. HAVARA is used to help rainfall data analysis using statistic approach. Rainfall model is used to vary the moisture content to model unsaturated soil condition. There are six rainfall models, consists of one steady state model and followed by five transient model to accomodate the pore water pressure changes due to rainfall. The results show that rainfall with intensity near saturated permeability of soil gives more significant influence in increasing pore water pressure and deformation than normal rainfall even with long duration. Proposed countermeasure by providing counterweight and subdrain do not significantly effect the deformation, but it could improves the safety factor significantly, so that the slope is more in stable condition. Keywords : landslide, unsaturated soil properties, pore water pressure, slope deformation, numerical simulation, finite element method, countermeasures.